Genetic Aspects of Morphological Examinationo of Fetuses from Multiple Pregnancies - Kurlej, Wiesław (Anthropological Review, 1983)
In contrast to numerous anatomic-anthropometric examinations of twins: during their postnatal life analogical examinations dealing with prenatal period are conducted only recently. In Poland no such examinations have been conducted at all. Investigations based on observation of twin fetuses are of a great, importance especially for elucidation of determinants of growth of internal organs hitherto dealt with only in a limited and irregular way. The author in relation to the start of examination of twin fetuses in Poland. gives a brief review of problems pertaining to such a study together with some comments of methodological nature concerning collection and elaboration of twin material. It is important for unification of examinations conducted of necessity by various researchers in various institutions. Twin fetuses are hard to obtain in larger quantities and numerous materials are necessary for properly conducted meaningful investigations. Those may be obtained by centralizing collection of data obtained in course of other investigations by various persons.